SIMULASI MANAJEMEN LALULINTAS UNTUK MENGURANGI KEMACETAN DI PERUMAHAN JEMUR ANDAYANI - Rudy Setiawan (Jurnal Transportasi, 2008)
Abstract The use of cars by students, as a primary mode for commuting to and from school, has profound effects on school parking requirements and traffic congestion at the peak hour, especially if the school is located inside the residential area, such as Jemur Andayani, This paper aims to recognize the effect of the implementation of various potentials local area traffic management in reducing traffic congestion in Jemur Andayani residential area. The Trafik Plan to analyze eight potentials of local area traffic management. Schemes presents two alternative solutions to alleviate traffic congestion, consisting of opening which are open the access of the new bridge to reduce trip distance (alternative 4) and implementing several traffic lights to control traffic movement at the major intersections (alternative 8). Keywords: local area traffic management, trafikplan.